Covid Conversations 3: Elizabeth LeCompte and Kate Valk. (August 2021) - LeCompte, Elizabeth; Valk, Kate; Shevtsova, Maria
Abstract : Elizabeth LeCompte co-founded The Wooster Group with like-minded pioneers in New York in 1975, leading and directing its collaborators as deaths, departures, and new arrivals have changed its composition and emphases over the decades, segueing into a world-wide uncertain present. Kate Valk joined in 1978, the last representative of The Wooster Group's foundational period, apart from LeCompte herself, who is still a key member of the company. References in this conversation are primarily to works after 2016. LeCompte briefly remarks on the importance of Since I Can Remember – one of the Group's ongoing works in progress in 2021 – as an archival project that draws on Valk's memory of how Nayatt School was made during her formative years. Having become, since then, a quintessential Wooster Group performer, Valk extended her artistic skills to stage direction, undertaking, most recently, The B-Side (2017). Both the initiative and idea for the piece came from performer Eric Berryman, who had brought Valk the collection of blues, songs, spirituals, and preachings on the 1965 LP made from the research of scholar folklorist Bruce Chapman. Berryman had been inspired to approach Valk because of her exclusive use of unadulterated historical recordings in Early Shaker Spirituals (2014), her directorial debut. The main work in rehearsal during 2020 and which was still locked down by the Covid-19 pandemic at the time of this conversation is The Mother, a Wooster Group variant of Brecht's dramatized version of Gorky's novel, directed by LeCompte. LeCompte discusses the current situation, emphasizing the increased vulnerability of independent artists and small-scale theatre, while giving a glimpse of the disadvantages for such groupings built into the North American system of project funding. The Wooster Group is a salient example of small-scale theatre that, despite continually precarious conditions, which the pandemic has highlighted and exacerbated, has achieved its creative goals and has defined its place in the exploratory avant-garde flourishing vigorously in the 1960s and 1970s. This particular avant-garde, LeCompte believes, has seen various important developments over the years but might well now be counting its last days. The conversation here presented was recorded on 31 October 2020, transcribed by Kunsang Kelden, and edited by Maria Shevtsova, Editor of New Theatre Quarterly.